New single-nucleotide polymorphisms associated with differences in platelet reactivity and their influence on survival in patients with type 2 diabetes treated with acetylsalicylic acid: an observational study - Milanowski, Lukasz (Acta Diabetol, 2016)
AIMS: Genetic polymorphisms may contribute to platelet reactivity in diabetic patients; however, the information on their influence on long-term antiplatelet therapy is lacking. Our aim was to evaluate the role of previously described genetic variants and platelet reactivity on risk of all-cause mortality and cardiovascular events. METHODS: Blood samples were obtained from 303 Caucasian patients. Genome-wide genotyping was performed using Illumina Human Omni 2.5-Quad microarrays, and individual genotyping of selected SNPs was performed using a custom Sequenom iPLEX assay in conjunction with the Mass ARRAY platform. Platelet reactivity was measured with VerifyNow Aspirin Assay and PFA-100 Assay. Univariate and multivariate Cox regression analyses were performed to determine the impact of genetic variants and platelets reactivity on risk of all-cause mortality and cardiovascular events. RESULTS: Among the 237 patients included in the follow-up, death from any cause occurred in 34 (14.3%) patients and cardiovascular events occurred in 51 (21.5%) patients within a median observation time of 71 months (5.9 years). In univariate analyses, significant association in the presence of minor alleles in TXBA2R (rs1131882) with primary (HR 2.54, 95% CI 1.15–5.60, p = 0.021) and secondary endpoint (HR 2.06, 95% CI 1.06–4.04, p = 0.034) was observed. In addition, multivariate analyses revealed the impact of this polymorphism on primary (HR 2.34, 95% CI 1.09–5.00, p = 0.029) and secondary endpoint (HR 1.89, 95% CI 1.00–3.57, p = 0.048). CONCLUSIONS: Results of the study demonstrate for the first time an association between genetic polymorphism within TXBA2R gene encoding platelet’s surface receptor and long-term survival of diabetic patients treated with ASA.